(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Obesity has a detrimental impact on most organ systems, including the reproductive system and leads to impairments in ovarian, follicular, and oocyte development, fertilization, and embryo development and implantation. The term "ovarian reserve" refers to the quantity and quality of a woman’s current reservoir of oocytes and is closely associated with reproductive potential. It naturally declines with age from puberty to menopause. Methods: 50 obese women and 50 non-obese women in the reproductive age group were selected in the study. Measured body mass index (BMI), anti-mullerian hormone (AMH), follicle-stimulating hormone (FSH), antral follicular count (AFC) and ovarian volume (OV) in both obese and non-obese women. The comparison of age and BMI, FSH and AMH, AFC and ovarian volume was done by using t test and P value less than 0.001 was considered statistically significant. Serum FSH and AMH levels were analyzed using radioimmunoassay (RIA) technique while AFC and ovarian volume were determined through transvaginal ultrasonography respectively. Results: This study showed statistically significant lower values of Anti-Müllerian Hormone (AMH), Antral Follicle Count (AFC), and ovarian volume, alongside higher values of Follicle-Stimulating Hormone (FSH), compared to the non-obese women of the same age group. Slightly elevated levels of serum FSH and lower levels of serum AMH, reduced Antral Follicle Count (AFC), and smaller ovarian volume, in obese women compared to non-obese women were shown. Conclusion: This study concludes that obese women exhibit lower AMH levels, AFC and Ovarian volume, along with higher FSH levels, compared to non-obese women of the same age group. These findings suggest that obesity has a detrimental effect on ovarian reserve markers and may impact reproductive health, emphasizing the importance of weight management for preserving fertility.